2021
DOI: 10.29065/usakead.887799
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinde Bilişsel Esneklik ve Duygu Düzenleme Becerilerinin İnternet Bağımlılığı Üzerindeki Yordayıcı Rolü

Abstract: Bu araştırmada, bilişsel esneklik ve duygu düzenleme becerileri değişkenlerinin üniversite öğrencilerinin internet bağımlılığı düzeylerini ne kadar yordadığı incelenmiştir. Araştırma ilişkisel tarama modelinde dayalı olarak yürütülmüştür. Çalışmanın araştırma grubunu 2020-2021 eğitim-öğretim yılında Türkiye'deki farklı üniversitelerde öğrenim gören 318 (%43.1) erkek, 420 (%56.9) kız olmak üzere toplam 738 öğrenci oluşturmuştur. Araştırma grubunun yaş ortalaması 20.19'dur. Araştırmada veri toplama araçları olar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(8 reference statements)
0
7
0
3
Order By: Relevance
“…At this point, healthy internet use of university students has a critical importance. It is thought that raising awareness about internet addiction and determining the variables associated with internet addiction are important in terms of preventive and curative mental health studies (1,3,4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this point, healthy internet use of university students has a critical importance. It is thought that raising awareness about internet addiction and determining the variables associated with internet addiction are important in terms of preventive and curative mental health studies (1,3,4).…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive and dysfunctional uses of the Internet causes certain problems. One of these negative outcomes is described as internet addiction (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, cognitive flexibility was thought to be negatively related to adverse conditions such as phubbing and social media addiction. Similarly, internet addiction (Ateş & Sağar, 2021), social media addiction (Sagar, 2021), and cognitive flexibility were negatively related. In addition, it has been found that smartphone use reduces cognitive flexibility (Hartanto & Yang, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…https://dergipark.org.tr/pub/egitim e-ISSN 2619-9351 tarafından yaygın bir biçimde kullanılabilir durumda olan internet, neredeyse yaşamın tüm alanlarına temas ederek, yaşamın vazgeçilmez bir parçası haline gelmiştir. Bu bağlamda yaşamda önemli bir konuma ve kitlelerce yaygın kullanıma sahip olan internet son derece dikkat çeken bir kavramdır (Ateş ve Sağar, 2021;Sağar, 2022a, Sağar ve Kök Eren, 2018Sağar ve Özabacı, 2022).…”
unclassified